Work under urgency and emergency and its relation with the health of nursing professionals El trabajo en urgencia y emergencia y su relación con la salud de los profesionales de enfermería O trabalho em urgência e emergência e a relação com a saúde das profissionais de enfermagem - Daiane Dal Pai; Liana Lautert (Universidade de São Paulo, 2008)
The study aimed at understanding work under urgent and emergency conditions and its connection with the health of nursing professionals, who work at an urgency and emergency state service. Descriptive qualitative case study carried out at a state service in Porto Alegre, RS. The collection of data included the analysis of documents from the Institution, the observation of the work dynamics, and the performance of semi-structured interviews with the nursing professionals. The data were submitted to content analysis. One could understand that the health of the nursing professionals is constituted from a working dynamics which is sometimes harmful because it results from an organizational context that carries marks of a state health system with many gaps, however, that allows the meaning of work to be an essential element for the ability to keep the balance and not getting sick in view of the work demands. El estudio tuvo por objetivo comprender el trabajo en urgencia y emergencia y su relación con la salud de los profesionales de enfermería, que trabajan en un servicio público de emergencia. Se trata de un estudio de caso, cualitativo descriptivo, realizado en un servicio público de Porto Alegre RS. La recolección de los datos incluyó el análisis de documentos de la institución, la observación en la dinámica del servicio y entrevistas semi-estructuradas con profesionales de enfermería. Los datos fueron procesados a través del método de análisis de contenido. Fue posible comprender que la salud de las profesionales de enfermería se constituye a partir de una dinámica de trabajo, que a veces daña la salud, producto de un contexto organizacional marcado por un sistema público de salud con muchos vacíos, sin embargo permite que el trabajo sea realizado como elemento fundamental, manteniendo así el equilibrio y no permitiendo la enfermedad frente a las exigencias laborales. O estudo objetivou compreender o trabalho em urgência e emergência na sua relação com a saúde das profissionais de enfermagem, atuantes em um serviço público de pronto-socorro. Trata-se de estudo de caso, qualitativo descritivo, realizado em um serviço público de Porto Alegre, RS. A coleta dos dados incluiu a análise de documentos da Instituição, a observação da dinâmica do serviço e a realização de entrevistas semi-estruturadas com as profissionais de enfermagem. Os dados foram submetidos ao método de análise de conteúdo. Pôde-se compreender que a saúde das trabalhadoras é constituída a partir de dinâmica de trabalho, por vezes danosa, resultante de contexto organizacional que carrega marcas de sistema público de saúde com muitas lacunas, mas permitindo que o sentido do trabalho atue como elemento fundamental para a capacidade de se manter o equilíbrio e não adoecer diante das exigências do trabalho.